Aplikasi Pengacak Soal Ujian Untuk Type Soal Berbasis Microsoft Word Menggunakan Metode Linear Congruent Method (LCM) - Limbong, Tonni; Taufik, Insan (MEANS (Media Informasi Analisa dan Sistem), 2017)
Exam questions made by lecturers in general in an educational institution around 99% are made from Microsoft Word applications. This happens because of the ability or skill of the question maker and the facilities of the institution. The exam questions that have been made seem like a consumable model, even though the material from these questions still has a relationship with the subject. With this condition the existing questions are not necessary and do not have to be destroyed, it should be stored and made into a question bank. So on the next examination the test questions stored in the bank questions to be randomized again to make new questions as many as the number of questions needed so that the exam questions are presented far from static and color and each test for each participant will never be the same as previous questions. and also the implementation of semi-computerized exams do not need to require a computer laboratory. This application is equipped with a randomization method, namely Linear Congruent Method (LCM), so that the questions that appear will never be the same each time printing a question in the form of executable (EXE), making it easier for study programs to make exam questions in multiple choices and in accordance with existing material in the syllabus and GBPP that apply from several lecturers who teach the same subject.